The myth of Ulisses in Se questo è un uomo - Mauro, Claudia Fernanda de Campos (Revista de Letras, 2013)
This study goes from the myth of Ulysses presented by Dante Alighieri up to Primo Levi’s reformulation of the last adventure of the Greek hero, in the context of his personal experience related to the Holocaust. It is a modern Ulysses that presents a modern vision of Hell. Dante’s Ulysses is among the souls that are convicted to pay for their sins for all eternity and, at the same time, witnesses and narrators, able to tell the process of their own death. In this sense, the Greek traveler became a symbol of the Holocaust memoirs written by Primo Levi, a symbol of the concentration camps. The chapter called Il canto di Ulisse, part of Levi’s Se questo è un uomo, is a classic example of the presence of Dante in the narrative of the Italian survivor . The myth of Ulysses is a symbol of the intelligent man on the threshold of the mystery of the human existence and, in Levi, it becomes a didactic instrument. To recite a poem assumes, in the universe of the concentration camp, the value of a political and human act, a collective affirmation of the values which that system wanted to destroy.